Librarians challenge in the future / Siti Aminah Zulkifli, Siti Nur Atika Ismail and Siti Rokayah Yaakop - Zulkifli, Siti Aminah; Ismail, Siti Nur Atikah; Yaakop, Siti Rokayah (Faculty of Information Management, 2014)
A ccording to (Merriam- Webster) librarian is a person who works in the library that responsible in managing the material in the library. They used to help the library user to find the materials needed from the library. That was previous definition for the librarian, whereas today, the situation is a bit different for the roles of librarian.